RIGHT VENTRICULAR LONGITUDINAL SYSTOLIC STRAIN AS A PREDICTION MARKER OF NEW ONSET HEART FAILURE WITH PRESERVED EJECTION FRACTION IN ESSENTIAL HYPERTENSION. (June 2022) - Zervakis, Stylianos; Marketou, Maria; Danelatos, Christos; Maragkoudakis, Spyros; Pateromichelakis, Themistoklis; Plevritaki, Anthoula; Savva, Eirini; Fragkiadakis, Kostas; Kladou, Eleni; Kampanieris, Emmanouil; Kassotakis, Spyros; Kalomoirakis, Petros; et al.
Abstract : Objective: Accurate assessment of right ventricular (RV) systolic function is important, as it is an established prognostic marker in cardiac diseases. Speckle-tracking echocardiography is a sensitive tool for detection of subclinical left ventricular impairment in essential hypertension. We associated RV function using longitudinal peak systolic strain (GLS) in patients with essential hypertension with the risk of future development of heart failure with preserved ejection fraction (HFpEF). Design and method: We performed a retrospective observational study that included 458 patients with essential hypertension (266 males, aged 63 ± 18 years) and 179 normotensives (100 males, aged 66 ± 15 years). Standard echocardiography was performed at the initial visit. 2D speckle tracking echocardiography with evaluation of longitudinal strain in each segment of the RV (basal: RVLS-B; mid: RVLS-M, apical: RVLS-A) and global RV free-wall strain (RVLS-G) were also performed. We studied the cases of new onset HFpEF in hypertensive patients. Results: The median follow up was 85 months (22–122). RVLS-G, RVLS-B and RVLS-M were significantly impaired in hypertensives compared to controls (RVLS-G: -16.1 ± 9.7 vs -20.0 ± 5.1, RVLS-B: -11.7 ± 3.7 vs -20.6 ± 3.3, RVLS-M:-16.3 ± 5.4 vs -20.7 ± 4.9, p < 0.05 for all). No significant difference was detected for the RVLS-A (-20.1 ± 3.8 for hypertensives vs -21.31 ± 6.5 for controls, p = NS). Thirty two hypertensive patients developed HFpEF (7 %). A cut-off RVLS-G worse than -17 % was significantly associated with new onset HFpEF (p < 0.001) in those patients. A multivariate Cox regression analysis showed that RVLS-G had independent significant prognostic value for the risk of HFpEF (HR: 10.5, 95% confidence interval (CI): 7.3–25.4). Conclusions: Essential hypertension leads to a decrease of RVLS which is strong predictor of a new onset HFpEF. Future studies are needed to assess the significance of these findings and the effects of treatment.